Developmental markers of ganglion cells in the enteric nervous system and their application for evaluation of Hirschsprung disease. (22nd August 2014) - Kawai, Hitomi; Satomi, Kaishi; Morishita, Yukio; Murata, Yoshihiko; Sugano, Masato; Nakano, Noriyuki; Noguchi, Masayuki
<x xml:space="preserve">Abstract</x> Hirschsprung disease (HSCR) is a congenital disease resulting from failure of neural crest‐derived ganglion cells to colonize the colon. Conventional diagnostic methods are insufficient for evaluating the 'functional' prognosis of HSCR. In order to elucidate the maturation of ganglion cells, 17 immunohistochemical markers were examined. We examined the digestive tracts of 2 human early delivery patients, 2 miniature swine fetuses, 4 little infants, 3 infants, 3 children, 6 adults, and 3 aged individuals. With increasing age, the labeling index (LI) for both calretinin and tyrosine hydroxylase (TH) increased, whereas that for SOX10 decreased. We then examined the 'transitional zone' of HSCR in 21 affected patients and 18 controls for these three markers. The LI of calretinin and TH were significantly lower than in the controls (median: 3.7 in HSCR and 8.2 in controls, P < 0.001, median: 27.9 in HSCR and 44.4 in controls, P < 0.001, respectively). In contrast, the LI for SOX10 showed no significant difference (median: 33.7 in HSCR and 29.2 in controls, P = 0.666) however, hierarchical cluster analysis was able to divide HSCR patients into two groups. These results suggest that immature ganglion cells are present in the transitional zone of HSCR, and that HSCR may have two different pathophysiological processes.